2010
DOI: 10.1007/s12022-010-9137-4
|View full text |Cite
|
Sign up to set email alerts
|

Muc-1 Expression May Help Characterize Thyroid Nodules but Does Not Predict Patients’ Outcome

Abstract: Our purpose was to evaluate MUC1 clinical utility in the diagnosis and prognosis of thyroid cancer patients. We studied the protein expression of MUC1 in 289 thyroid carcinomas and 121 noncancerous thyroid nodules. There were 41 follicular carcinomas (FC) and 248 papillary thyroid carcinomas (PTC) including 149 classic (CPTC), 20 tall cell (TCPTC) and 79 follicular variants (FVPTC). In addition, we used a quantitative real-time PCR (q-PCR) method to measure MUC1 mRNA expression levels in 108 carcinomas, 23 hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…Briefly, each tissue spot was digitalized through the system software, and a numerical value proportional to the percentage of stained nuclei was attributed by the computer analysis, as previously reported by our group [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Briefly, each tissue spot was digitalized through the system software, and a numerical value proportional to the percentage of stained nuclei was attributed by the computer analysis, as previously reported by our group [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the system attributes a numerical value proportional to the intensity and extension of brown staining of digitalized images using the following formula: scoreZ(intensity !brown area)/(brown areaCblue area). Each spot is assessed in triplicate and the final value is given by the mean of triplicates, as previously reported (Minot et al 2009, Morari et al 2010. Aiming to perform survival analysis, staining %median was considered negative and staining Omedian was considered positive, as described previously (Cunha et al 2012b).…”
Section: Immunohistochemical Evaluationmentioning
confidence: 99%
“…In fact, a correlation between the protein expression profile and immune cell infiltration in DTC was observed (Bruland et al 2009). Some researchers have suggested that MUC1, NIS (SLC5A5), ATM, PTEN, and CD56 (NCAM1) expression might indicate tumor differentiation and tumor progression, demonstrating tumor antigenicity (Larson et al 2007, Morari et al 2010. However, whether these markers are really associated with DTC immune response is still not clear.…”
Section: Infiltration Of a Mixture Of Different Immune Cells May Be Rmentioning
confidence: 99%
“…1, panel I. Tumor markers included CD56, NIS, MUC1, PTEN, ATM, and B7H1 (CD274). IHC procedure was held as described previously running positive and negative controls in the same batch of reactions (Morari et al 2010).…”
Section: Infiltration Of a Mixture Of Different Immune Cells May Be Rmentioning
confidence: 99%